Evaluating the effectiveness of home exercise programmes using an online exercise prescription tool in children with cerebral palsy: protocol for a randomised controlled trial. - Johnson, R.; Williams, Sian; Gucciardi, D.; Bear, N.; Gibson, N. (BM J Group, 2018)
Introduction: Children with cerebral palsy (CP) and other neurodevelopmental disabilities often receive a home programme of exercises to assist in reaching their therapy goals. Adherence to exercise programmes is necessary to attain the level of practice required to achieve goals; however, adherence can be difficult to accomplish. In this paper, we describe the protocol for a randomised controlled trial to evaluate the effectiveness of delivering a home exercise programme to school-age children with disabilities using Physitrack, an online exercise prescription tool with a website or app interface. Methods and analysis: Participants aged 6–17 years, with CP or other neurodevelopmental disabilities, receiving community physiotherapy services in Western Australia, will be recruited. Participants will be stratified by age and functional mobility and randomised to either the intervention group, who will complete an 8-week home exercise programme using Physitrack, or the control group, who will complete an 8-week exercise programme without Physitrack. Researcher blinding to group allocation, and participant blinding to outcome, will be maintained. The primary outcome measures are adherence to the home exercise programme with weekly collection of home exercise logs; achievement of individualised goals by phone interview before and after intervention; and correctness of exercise performance by collection and analysis of videos of participants performing home exercises. Secondary outcome measures include enjoyment of physical activity, confidence to complete exercise programme, preferred method of delivery of programme and usability of Physitrack. A sample size of 58 participants will be necessary to see an effect on home programme adherence. Data will be analysed using the intention-to-treat principle. Ethics and dissemination: Ethical approval was obtained from Curtin University Human Research Ethics Committee in July 2016 (10391). Outcomes will be disseminated through publication in peer-reviewed journals and presentations at scientific conferences. Trial registration number: ACTRN12616000743460; Pre-results.